2023
DOI: 10.1111/ajsp.12564
|View full text |Cite
|
Sign up to set email alerts
|

“Celebrities to lean on!” Perceived celebrity support across two cultures—Iran and the United States

Abstract: Though many people loathe celebrities and their lifestyles, celebrities can also be perceived as being available to provide community support. The purpose of this study was to establish the psychometric properties of the Perceived Celebrity Support Inventory. The scale was developed to capture three aspects of perceived celebrity support to the community: instrumental (i.e., providing tangible and concrete assistance), informational (i.e., advice, explanation, and information), and emotional (i.e., empathizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Scholars have carried out some studies on the attributes of internet influencers that affect customer attitude and behavior (T. Y. Chen et al, 2021;Ouvrein et al, 2021;Shabahang et al, 2023), and suggested that influencers' attributes drive their success (L. Wang et al, 2021). We define internet influencers' attributes as professionalism, credibility, interactivity, and attractiveness in this study, which originate from the study of F. , and have been applied in some studies, such as the study by L. Wang et al (2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have carried out some studies on the attributes of internet influencers that affect customer attitude and behavior (T. Y. Chen et al, 2021;Ouvrein et al, 2021;Shabahang et al, 2023), and suggested that influencers' attributes drive their success (L. Wang et al, 2021). We define internet influencers' attributes as professionalism, credibility, interactivity, and attractiveness in this study, which originate from the study of F. , and have been applied in some studies, such as the study by L. Wang et al (2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars have carried out some studies on the attributes of internet influencers that affect customer attitude and behavior (T. Y. Chen et al, 2021; Ouvrein et al, 2021; Shabahang et al, 2023), and suggested that influencers’ attributes drive their success (L. Wang et al, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%